The Effect of Rootone F Concentration and Planting Media Composition on the Growth of Fig (Ficus carica L.) Cuttings - Intan Febriana Samodro; Sutini Sutini; Ramdan Hidayat (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Fig cuttings often face problems with failure of the roots to grow from the cuttings, so efforts are needed to encourage root induction by administering auxin growth regulators. Rootone F is an exogenous PGR from the auxin group which can stimulate root growth. In order for the roots to grow, develop and function well, plants need an ideal planting medium. The ideal planting medium to support good growth of plant seeds is a proportional composition of physical, chemical and biological elements. The aim of the research was to examine the combined effect of Rootone F concentration and planting media composition on the vegetative growth of fig cuttings. The research consisted of two treatment factors, namely the concentration of Rootone F (0 ppm (Control), 100 ppm, 150 ppm and 200 ppm) and the composition of the planting media (soil: husk charcoal: cow manure) with a ratio (1:1:1), (2:1:1), and (3:1:1). The best treatment combination is 150 ppm Rootone F and planting media mixed with soil: roasted husks: organic cow fertilizer with a ratio of 3:1:1 which has a significant effect on shoot length, root length, fresh weight of roots and percentage of live cuttings (%). A concentration of 100 ppm Rootone F gave the best results when the first shoots appeared (DAT), a concentration of 150 ppm Rootone F gave the best results on the number of leaves. A planting medium composition of (3:1:1) gives the best results when the first shoots appear (DAT).   Keywords: Auxin, Growth regulator, Influence, Nutrient, Vegetative.